1999
DOI: 10.1177/1088767999003004003
|View full text |Cite
|
Sign up to set email alerts
|

Stalking and Intimate Partner Femicide

Abstract: An 18-item stalking inventory and personal interviews with knowledgeable proxy infor-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
173
1
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(188 citation statements)
references
References 22 publications
(19 reference statements)
6
173
1
8
Order By: Relevance
“…They also found that the risk of intimate partner femicide increased by five times when the victim left the abusive partner for another man or when sexual jealousy was triggered . Additional empirical evidence has suggested increased risk of intimate partner femicide in response to the victim's attempt to leave the relationship (e.g., McFarlane et al, 1999;Nicolaidis et al, 2003; U.S. Department of Justice, 1998). Campbell et al also documented that having a child from the victim's previous partner living in the home doubled the risk of intimate partner femicide.…”
Section: Intimate Partner Homicidementioning
confidence: 99%
“…They also found that the risk of intimate partner femicide increased by five times when the victim left the abusive partner for another man or when sexual jealousy was triggered . Additional empirical evidence has suggested increased risk of intimate partner femicide in response to the victim's attempt to leave the relationship (e.g., McFarlane et al, 1999;Nicolaidis et al, 2003; U.S. Department of Justice, 1998). Campbell et al also documented that having a child from the victim's previous partner living in the home doubled the risk of intimate partner femicide.…”
Section: Intimate Partner Homicidementioning
confidence: 99%
“…In general, helping professionals often place the responsibility for making changes on the woman, and they often suggest that the only appropriate change to be made is to leave the violent relationship (Dunn & Powell-Williams, 2007). This can be particularly problematic as separation has been proven a significant risk factor for lethality in cases of battering ) Campbell et al, 2003McFarlane et al, 1999). …”
Section: Counseling For Women Who Have Been Batteredmentioning
confidence: 99%
“…De un lado, la distancia propicia conductas de acoso. El acoso y su intensidad y frecuencia están fuertemente asociados con intentos de homicidio (McFarlane et al, 1999). Una investigación en Estados Unidos identificó que el riesgo de feminicidio es mayor luego de la separación que dentro de la relación de pareja (Johnson y Hotton, 2003).…”
Section: El Feminicidio Desde Lo Microsocialunclassified